2016
DOI: 10.1161/strokeaha.115.011196
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Nonatherosclerotic Internal Elastic Lamina Calcification in the Intracranial Internal Carotid Artery

Abstract: Background and Purpose-Calcification of the intracranial internal carotid artery (iICA) is an independent risk factor for stroke. These calcifications are generally seen as manifestation of atherosclerosis, but histological investigations are limited. The aim of this study is to determine whether calcifications in the iICA are present in atherosclerotic plaques, or in other parts of the arterial wall. Methods-Thirty-nine iICAs were histologically assessed, using digital microscopy to quantify the amount of cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 11 publications
5
62
1
Order By: Relevance
“…[3] Three, medial calcification was found to comprise 71% of the dominant calcification burden and thereby it’s influence on physiopathology may be underestimated. [5] Four, clinically medial calcification is mostly thought to be a passive and chronic process, however, in a recent review it was shown that it is actually an active process resembling bone formation. [7] The limited knowledge on the clinical consequences and therapeutic options for medial calcification mainly comes from genetic syndromes and epidemiological studies outside the brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Three, medial calcification was found to comprise 71% of the dominant calcification burden and thereby it’s influence on physiopathology may be underestimated. [5] Four, clinically medial calcification is mostly thought to be a passive and chronic process, however, in a recent review it was shown that it is actually an active process resembling bone formation. [7] The limited knowledge on the clinical consequences and therapeutic options for medial calcification mainly comes from genetic syndromes and epidemiological studies outside the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The arteries were divided in a proximal (C4 and C5 according to the classification system proposed by Bouthillier) and a distal (C6) segment (S1 Fig),[14] the intersection was perpendicular to the lumen Per segment, 2–3 histological slides, stained with hematoxylin and eosin and elastin van Giesson, were used to digitally analyse the total surface of calcifications in the intima, in the media and around the internal elastic lamina, as previously described. [5] Calcifications were characterized by quite sharp demarcated, acellular spots and areas, which were dark pink to purple colored on hematoxylin and eosin stained slides. For this study digital images of 142 slides were available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DSA can depict stenotic lesions in large, as well as small arteries, including the A2 segment of the anterior cerebral artery, M2-M3 segments of the middle cerebral artery (MCA), P2 segment of the posterior cerebral artery, and even more peripheral segments of the intracranial arteries. With unenhanced CT, arterial VW calcifications can be detected that are associated with future stroke risk (10)(11)(12)(13). CT angiography is an easily accessible and fast procedure in patients with acute stroke and can depict stenotic lesions very accurately in the more proximal intracranial arteries and its branches (14).…”
Section: Vw Imaging Sequence Prerequisitesmentioning
confidence: 99%
“…Mechanisms underlying remain largely unknown, but it may be hypothesized that those patients with a higher burden of ICAC generally also have a worse condition of vessels more distal in the brain. 16,17 In addition, aside from intimal calcification, calcification of the internal elastic lamina 18 also occurs relatively commonly in the intracranial part of the internal carotid artery. This arterial stiffening may directly result in increased pulse pressure leading to damage in the microvasculature and surrounding tissue.…”
Section: February 2017mentioning
confidence: 99%